Assessment of the physical condition levels of schoolchildren aged 11-12 years, through the application of the ALPHAFITNES Battery - Martínez Martínez, J.; de los Reyes-Corcuera, M.; Borrell-Lizana, V.; Pastor-Vicedo, J. C. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The state of health in the schoolchildren shows a high rate of sedentary lifestyle and therefore it is necessary to know the state of health of schoolchildren and use the concepts in a correct way in order to be able to apply a precise intervention. The aim of this study is the health status in schoolchildren aged 11 to 12 years using the ALPHA-Fitness battery. The sample consists of 79 subjects, 38 boys and 41 girls. The results show how the levels of fitness related to health are low or very low of those established for the age of 13 years. An interventional work based on the improvement of the physical condition is necessary and more in the girls than in the boys.